Effects of ozone and produced hydroxyl radicals on the transformation of graphene oxide in aqueous media. Issue 8 (4th July 2019) - Du, Tingting; Adeleye, Adeyemi S.; Zhang, Tong; Yang, Nan; Hao, Rongjie; Li, Yao; Song, Weihua; Chen, Wei
Abstract : The hydroxyl radicals and ozone play different roles in ozonation of GO. Abstract : The rapidly increasing applications of graphene oxide (GO) will lead to its release into the natural environment. To date, the fate and transformation of GO in water and wastewater treatment systems are not well understood. In this study, we investigate the mechanism of GO ozonation and probe the individual roles of oxidants such as ozone (O3 ) and hydroxyl radicals. We looked at the effects of the oxidants (ozone and hydroxyl radicals) on functionalized and unfunctionalized aromatic rings (using carbonaceous nanomaterials with different degrees of oxidation). Multiple characterization methods, including transmission electron microscopy (TEM), scanning electron microscopy (SEM), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared (FTIR) and Raman spectroscopy, were used to investigate the physicochemical changes of GO upon ozonation. The hydroxyl radical (˙OH)—formed from aqueous O3 —hydroxylated GO. The combination of ˙OH/O3 further oxidized the functionalized aromatic rings of GO and their C–O groups (to CO and O–CO), cleaving some of the aromatic rings of GO. When ˙OH was quenched, O3 had no observable effects on the unfunctionalized aromatic rings, which are more predominant on reduced GO and graphene. Microscopy analyses showed that ozonation led to crumpling of GO nanosheets, truncation of GO edges, formation of holes (diameter = 5–15 nm), and production of small-sized graphenic fragments. The changes in GO surface functional groups and hydrophobicity induced by ozonation affected the transport properties of GO in porous media, as well as its adsorption affinities for model organic contaminants.